Potencial fisiológico de sementes de melão por meio da análise automatizada (vigor-s) - Leite, Moadir de Sousa (2020)
Melon is a vegetable of great food and nutritional importance, which is why its cultivation has been growing worldwide. As a result, investments in technologies will be needed, especially regarding the quality of seeds used in the establishment of new areas. In this sense, the objective was to verify the effectiveness of the Automated Analysis of Seed Vigor system (Vigor-S) in evaluating the physiological potential of melon seeds. Eight seed lots were used; four from the Supreme hybrid and four from the Premier. The physiological potential of the seeds was initially measured by the following tests : germination; first germination count; shoot and root length and total dry mass of seedlings from the germination test; seedling emergence; emergency speed index; shoot dry mass of emerged seedlings; electric conductivity; potassium leaching; controlled deterioration; traditional accelerated aging; accelerated aging in saturated NaCl solution; and automated analysis of seed vigor (Vigor-S), which included the analysis of seedlings from the germination test, traditional accelerated aging and accelerated aging in saturated NaCl solution. The experiment was conducted in a completely randomized design, with five replications. Data were subjected to analysis of variance and means compared by Tukey test. Pearson's simple correlation was also performed between traditional vigor test results and automated analysis of seed vigor (Vigor-S). The results indicated the effectiveness of the automated analysis system, especially when it was used together with the tests of traditional accelerated aging and in saturated NaCl solution, with results similar to those obtained in the traditional vigor tests. Thus, it is concluded that the Automated Analysis of Seed Vigor system (Vigor-S) is effective in evaluating the physiological potential of melon seeds.